Effect of testosterone on lipid metabolism and endothelium in men with type 2 diabetes mellitus and hypogonadism. (25th November 2020) - Khripun, I; Vorobyev, S; Khripun, A; Kogan, M; Demidova, A; Belousov, I
Abstract: Background: To date, knowledge about the effects of testosterone (T) on the cardiovascular system of men remains controversial and requires additional research. Especially the putative impact of T replacement therapy (TRT) on lipid metabolism and endothelial dysfunction as a starting mechanism for the development of cardiovascular pathology in men with type 2 diabetes mellitus (T2DM) presenting with T deficiency has to be elucidated. The aim of this work was to evaluate the effect of T replacement therapy on lipid metabolism and function of endothelium in men with T2DM and hypogonadism. Methods: The study included 95 men (mean age 55, 3±2, 4 years) with T2DM and late onset hypogonadism, established according to EAU 2015 criteria. Parameters of carbohydrate and lipid metabolism, as well as ultrasound assessment of flow-mediated dilatation of the brachial artery (FMD-BA) and intima-media thickness (IMT) of brachial arteries were performed at baseline and after 9 months. Patients were randomized into 2 groups: 1 - 45 men receiving TRT, using 1% transdermal T-gel and 2 (control group) - 50 men, who were not assigned to TRT. Statistical analysis was carried out using the Wilcoxon - test for repeated measurements (STATISTICA 10 software package). Results: During the treatment period no serious adverse events were registered. The study revealed a significant decrease in HbA1c (p<0.001), total cholesterol (p=0.009), triglycerides (p=0.004) and LDL (p=0.01) levels as well as an increase in HDL level (p=0.001) in the 1st group vs baseline and compared to the 2nd one. There was a decrease in IMT (from 1.0 [0.8; 1.1] to 0.7 [0.6; 0.9] mm, p=0.002) in the 1st group compared to the 2nd (p<0.001). The endothelium-dependent FMD-BA increased 1.5 - fold in men applying T-Gel vs baseline as well as compared to the control group at the time point of follow- up (p<0.001). At the same time TRT leaded to acceleration of the time until maximal vasodilation – it became twice faster (from 120 [90; 120] to 60 [60; 90] sec, p<0.001) compared to baseline and the 2nd group (p<0.001). Linear blood flow velocity increased markedly in the 1st group compared to the 2nd at the time point of follow-up (p=0.03). Conclusion: TRT in men with T2DM and T deficiency leads to an improvement in carbohydrate and lipid metabolism together with a significant decrease in IMT and enhancement of endothelium vasomotor function, seems to facilitate a reduction in cardiovascular risk. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): Russian Science Foundation